EFEKTIVITAS PEMBERIAN TRUNK EXERCISE PADA PLANTAR FLEXOR ANKLE EXERCISE TERHADAP KEMAMPUAN BERJALAN ANAK CEREBRAL PALSY DIPLEGI (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2019)
AbstractObjective: To determine the difference in effectiveness between trunk exercise with plantar flexor ankle exercise and plantar flexor ankle exercise on the walking ability of children with cerebral palsy diplegi. Method: An experimental study with a pre-post-test design. The total sample in this study were 10 people who were divided into 2 groups and each group numbered 5 people. Group I with plantar flexor ankle exercise intervention and group II with the addition of trunk exercise to plantar flexor ankle exercise. The value of walking ability is measured by 1-minute walk test. Results: Test hypotheses I and II with paired sample t-tests showed p values <0.002 and p <0.001. This means that the provision of intervention groups I and II can significantly improve the ability to walk. Furthermore, hypothesis III between two groups with independent sample t-test obtained p value <0.004, meaning that there is a significant difference between group I and group II and this study shows that the addition of trunk exercise in plantar flexor ankle exercise is better than plantar flexor ankle exercise alone with differences in the average difference and standard deviation of 9.11 ± 2.75 in group I and 11.84 ± 2.05 in group II. Conclusion: there is a difference between plantar flexor ankle exercise and giving trunk exercise to plantar flexor ankle exercise can improve walking ability. Keywords: Cerebral palsy, plantar flexor ankle exercise, trunk exercise Abstrak Tujuan : Untuk mengetahui perbedaan efektivitas antara trunk exercise dengan plantar flexor ankle exercise dan plantar flexor ankle exercise terhadap kemampuan berjalan anak cerebral palsy diplegi. Metode  : Penelitian bersifat eksperimental dengan pre test-post test desain. Total sampel dalam penelitian ini adalah 10 orang yang dibagi menjadi 2 kelompok dan tiap kelompok berjumlah 5 orang. Kelompok I dengan intervensi plantar flexor ankle exercise dan kelompok II dengan penambahan trunk exercise pada plantar flexor ankle exercise. Nilai kemampuan berjalan diukur dengan 1-minutes walk test.  Hasil : Uji hipotesis I dan II dengan paired sample t-test menunjukkan nilai p<0,002 dan p<0,001. Hal ini berarti pemberian intervensi kelompok I dan II secara signifikan dapat meningkatkan kemampuan berjalan. Selanjutnya, hipotesis III antara dua kelompok dengan independent sample t-test diperoleh nilai p<0,004, artinya terdapat perbedaan yang signifikan antara kelompok I dan kelompok II dan penelitian ini menunjukkan penambahan trunk exercise pada plantar flexor ankle exercise lebih baik daripada plantar flexor ankle exercise saja dengan perbedaan rata-rata selisih dan standar deviasi sebesar 9,11±2,75 pada kelompok I dan 11,84±2,05 pada kelompok II. Kesimpulan : ada perbedaan antara plantar plantar flexor ankle exercise dan pemberian trunk exercise pada plantar flexor ankle exercise dapat meningkatkan kemampuan berjalan. Kata kunci: Cerebral palsy, plantar flexor ankle exercise, trunk exercise